Ecotoxicological Diagnosis in the Tanning Industry - Mwinyihija, Mwinyikione; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
With a wide experience spanning over thirty years in the Leather subsector Dr. M Mwinyihija embarked on his doctoral studies at the University of Aberdeen, focusing on the latest ecotoxicological and novel techniques that could provide environmental diagnostic insights to the tanning industry. Certain criterion was fundamental in writing this book; that the tanning industry is a major source of pollution worldwide, particularly in developing countries. Indeed the developed ecotoxicological and analytical techniques were deliberately designed on the basis of being rapid, simple and inexpensive and directed towards resolving the tanning industry challenges on terrestrial and aquatic systems. Thus the resultant research data reported, incorporates both field related and laboratory based techniques to address underlying environmental problems in the tanning sector.
Main Pollutants and Environmental Impacts of the Tanning Industry -- Ecotoxicological Techniques and Assessment of Environmental Samples -- Occupational Risk in the Tanning Industry -- Ecological Risk Assessment (ERA) of a Tanning Industry -- General Discussion.
Keywords: Environmental sciences; Radiotherapy; Cancer -- Surgery; Environmental toxicology; Environment; Ecotoxicology; Radiotherapy; Surgical Oncology